2013
DOI: 10.3347/kjp.2013.51.2.203
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Naegleria fowleri Meningoencephalitis in Taiwan

Abstract: After bathing at a hot spring resort, a 75-year-old man presented to the emergency department because of seizure-like attack with loss of conscious. This is the first case of primary amebic meningoencephalitis (PAM) caused by Naegleria fowleri in Taiwan. PAM was diagnosed based on detection of actively motile trophozoites in cerebrospinal fluid using a wet-mount smear and the Liu's stain. The amoebae were further confirmed by PCR and gene sequencing. In spite of administering amphotericin B treatment, the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Two studies were from China: [ 33 , 34 ]. The remaining studies were from Australia [ 35 ], Bangladesh [ 36 ], Nepal [ 37 ], Norway [ 38 ], Pakistan [ 39 ], Taiwan [ 40 ], Turkey [ 41 ], and Zambia [ 42 ]. A total of 16 (72.7%) patients included in this study died.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were from China: [ 33 , 34 ]. The remaining studies were from Australia [ 35 ], Bangladesh [ 36 ], Nepal [ 37 ], Norway [ 38 ], Pakistan [ 39 ], Taiwan [ 40 ], Turkey [ 41 ], and Zambia [ 42 ]. A total of 16 (72.7%) patients included in this study died.…”
Section: Resultsmentioning
confidence: 99%
“…The present review identified 13 published studies reporting detection of free-living amoebae in pool waters in tropical countries [77,84,85,86,87,88,89,90,91,92,93,94,95] (Table 2). The earlier survey appeared in 1983 [84] and reported the presence of pathogenic and free-living amoebae in swimming pool waters of Mexico City.…”
Section: Resultsmentioning
confidence: 99%
“…Among the organisms isolated, in their cystic or in their trophic stage, were Naegleria fowleri Carter and Acanthamoeba castellanii Douglas [84]. One study in Taiwan reported a fatality caused after swimming in hot springs [85]. The most recent one was carried out in two swimming pools in Alexandria (Egypt) [86].…”
Section: Resultsmentioning
confidence: 99%
“…Good cooperation from researchers, bathing managers, and agencies authorized to monitor sanitation and quality of bathing water is required; health care centers and laboratories to get surveillance of diseases, risk factors, and efforts to prevent the occurrence of similar cases due to activities in public hot springs. Some literature states that strict action was imposed by the local government on providers of hot spring tours when infection cases were reported, such as in Japan, Taiwan, and Costa Rica (24,25,28,29). This positive effort is very meaningful to support the growing hot spring tourism industry while still prioritizing safety, health, and the comfort of visitors to hot spring tours.…”
Section: Discussionmentioning
confidence: 99%